Targeting lyn kinase in chorea-acanthocytosis: A translational treatment approach in a rare disease - Peikert, Kevin; Glass, Hannes; Federti, Enrica; Matte, Alessandro; Pelzl, Lisann; Akguen, Katja; Ziemssen, Tjalf; Ordemann, Rainer; Lang, Florian; De Franceschi, Lucia; Hermann, Andreas; et al. (Journal of Personalized Medicine, 2021)
Background: Chorea-acanthocytosis (ChAc) is a neurodegenerative disease caused by mutations in the VPS13A gene. It is characterized by several neurological symptoms and the appearance of acanthocytes. Elevated tyrosine kinase Lyn activity has been recently identified as one of the key pathophysiological mechanisms in this disease, and therefore represents a promising drug target. Methods: We evaluated an individual off-label treatment with the tyrosine kinase inhibitor dasatinib (100 mg/d, 25.8–50.4 weeks) of three ChAc patients. Alongside thorough safety monitoring, we assessed motor and non-motor scales (e.g., MDS-UPDRS, UHDRS, quality of life) as well as routine and experimental laboratory parameters (e.g., serum neurofilament, Lyn kinase activity, actin cytoskeleton in red blood cells). Results: Dasatinib appeared to be reasonably safe. The clinical parameters remained stable without significant improvement or deterioration. Regain of deep tendon reflexes was observed in one patient. Creatine kinase, serum neurofilament levels, and acanthocyte count did not reveal consistent effects. However, a reduction of initially elevated Lyn kinase activity and accumulated autophagy markers, as well as a partial restoration of the actin cytoskeleton, was found in red blood cells. Conclusions: We report on the first treatment approach with disease-modifying intention in ChAc. The experimental parameters indicate target engagement in red blood cells, while clinical effects on the central nervous system could not be proven within a rather short treatment time. Limited knowledge on the natural history of ChAc and the lack of appropriate biomarkers remain major barriers for “clinical trial readiness”. We suggest a panel of outcome parameters for future clinical trials in ChAc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: ChAc; Dasatinib; Neuroacanthocytosis; Off-label; TKI